الظواهر اللغوية (المشترك والترادف والتضاد) في شروح ديوان الحماسة: LINGUISTIC PHENOMENA (HOMONYMY, SYNONYMY, AND ANTONYMY) IN THE COMMENTARIES OF DIWAN AL-HAMASAH (Al-Aasar, 2025)
The original principle in language is that a single word is assigned to a single meaning, but circumstances arise in language that lead to multiple words for one meaning, or multiple meanings for a single word. Linguists refer to words that convey a single meaning as "synonyms," while they refer to words that express different meanings as "homonyms." They also refer to words with opposite meanings as "antonyms."We have attempted to study these linguistic phenomena through the explanations of the Diwan of Al-Hamasa by Abu Tammam, mentioning the statements of both the proponents and opponents, along with their detailed evidence.The research reveals that the commentators on Diwan al-Hamasa discussed the phenomena of homonymy, synonymy, and antonymy. It also became clear that there is no dispute among Arab linguists regarding the existence of homonymy in the Arabic language, although some have narrowed its boundaries, excluding anything that can be attributed to a single general meaning.They differed regarding the existence of antonyms; some affirmed them, while others denied them. As for those who affirmed antonyms, they are many, but they differ in expanding or restricting the concept of the term.Linguists have disagreed about the occurrence of complete synonymy in Arabic. Since the beginning of the collection of the Arabic language, scholars have classified this linguistic material into various categories. Some went to great lengths in collecting those expressions, and this exaggeration led to the emergence of another group of scholars who opposed this trend and completely rejected the phenomenon of synonymy in Arabic. The correct view is that these phenomena should not be entirely denied, nor should they be excessively expanded.